Design and validation of art teaching pattern in elementary school of Iran - Mirshekari, Zeinab; Sa'adatmand, Zohreh; Keshtiaray, Narges (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this research is to design and validate the model of teaching appropriate art for primary school students in Iran.Methodology: The present research is applied in terms of practical purpose, descriptive correlation in terms of data collection and content analysis in terms of qualitative research method and using textbooks and articles of journals and conferences, in order to extract dimensions, components and indicators of learning environment. There has been a change in learning. Then, the experts of educational sciences and psychology, using the Delphi method, after discovering, rejecting or confirming the discovered components, and after calculating the validity and reliability of the researcher-made questionnaire made from the dimensions, components and indicators obtained, provide a qualitative model of art education model. Was.Findings: The results of the present study were based on a model of 61 themes as basic themes and 24 organized themes and 7 comprehensive themes were extracted. Based on the results of this model, 7 indicators of art teaching model include teaching method index including group and individual dimensions, student index which includes dimensions of knowledge, attitude, skill, intelligence and thinking, teacher index which includes dimensions of teaching method, scientific development and promotion. , An index of opportunities that includes the dimensions of culture, heritage, art and art in society, an index of weaknesses that includes the dimensions of parents, education, time, equipment and books and an index of strengths that includes upstream documents and the status of art and finally an index of principles that includes The principle of moderation, the principle of creation, the combination of art with the goals and the principle of freedom.Conclosion: Through the teaching of art, children's skills, creativity, talent, intelligence and imagination can be explored and hidden points in the child's mind can be discovered.